Efektivitas Program Pemberian Makanan Tambahan (PMT) Lokal Terhadap Peningkatan Berat Badan Balita Underweight dan Wasting - Wijayanti, Amanda Dwi; Zulaekah, Siti; Sudaryanto, Ruli (Universitas Tadulako, 2025)
Children under five in underdeveloped nations continue to suffer from nutritional issues brought on by nutritional inadequacies, such as underweight and wasting. The goal of Local Supplementary Feeding (PMT), a type of nutrient-rich food supplementation, is to improve the nutritional status of children between the ages of 6 and 59 months. This study aims to assess how well local supplemental feeding (PMT) programs raise the weight of toddlers who are underweight and wasting. One group was used in this quasi-experimental study's pretest-posttest design. Purposive sampling was used to choose 35 children between the ages of 12 and 59 months, 18 of whom had underweight issues and 17 of whom had wasting issues. Each toddler received a local PMT for 28 days to measure weight gain. The Paired Sample T-Test was used for statistical analysis because the data fit the normal distribution. Local PMT significantly raised body weight in both the underweight group (p = 0.002) and the wasting group (p = 0.005), according to paired sample t-test analysis. However, using an independent sample t-test to compare the effectiveness between the groups with the value of change (Δ) in body weight, the results were p = 0.108 (p > 0.05). This implies that the two groups' weight growth did not differ much. Local PMT administration for 28 days was shown to significantly increase body weight in underweight and wasting toddlers. However, comparative analysis of weight change between groups showed no statistically significant difference (p > 0.05), so the effectiveness of PMT can be considered similar in both nutritional conditions.